Anxiety-dependent modulation of motor responses to pain expectancy. Issue 3 (8th January 2018) - Fossataro, Carlotta; Bucchioni, Giulia; D'Agata, Federico; Bruno, Valentina; Morese, Rosalba; Krystkowiak, Pierre; Garbarini, Francesca
Abstract: The relationship between pain expectancy and motor system plays a crucial role in the human defensive system. Here, we took advantage of the inhibitory modulation of the motor pathway to the muscle of the hand receiving painful stimuli, by recording motor-evoked potentials (MEPs) to Transcranial Magnetic Stimulation (TMS). We employed a classical conditioning paradigm in which neutral (visual and auditory) stimuli were conditioned by pairing either painful or not-painful stimuli (electric shocks) in separated groups. Only the Pain Group showed clear motor responses: i.e. a significant decrease in MEPs amplitude, with respect to the neutral condition, not only in conditioning stimuli, when actual shocks were paired with neutral stimuli, but also in conditioned stimuli, when shocks were only expected. Significant differences between the two groups suggest that the MEPs decrease is specific for pain expectancy and does not pertain to anticipation in general. Furthermore, in the Pain Group, a significant negative correlation between physiological responses to conditioned stimuli and the participants' anxiety traits was found: the lower the MEPs amplitude, the higher the participants' anxiety scores. The present findings suggest that, in order for defensive motor responses to occur, actual pain is not necessary; rather, anxiety-dependent pain expectancy can be sufficient.